Resistance patterns to salinity and temperature in an estuarine mysid (Mysidopsis bahia) in relation to its life cycle - CHARLES, L., MCKENNEY, JR. (Comp. Biochem. Physiol. Vol. 109a, 199-208, 1994)
M703
NeMys doc_id: 3568